Pengaruh Efisiensi Waktu Tunggu, Biaya Pelayanan, Kebersihan, serta Kenyamanan Ruangan terhadap Kepuasan Pasien (Studi Pada Pelayanan Instalasi Rawat Jalan Rumah Sakit Medika Lestari) - Firdaus Razie Sugondo; Puspita Faustina; Innocentius Bernarto (Jurnal Manajemen Kesehatan Indonesia, 2021)
Seeing the importance of patient adherence in a patient's therapeutic journey and several factors related to patient adherence, we tried to assess patient satisfaction with the outpatient unit of Medika Lestari Hospital in 2021. Therefore, we conducted a cross-sectional study of patients aged 18–59 years to assess their satisfaction with the services of the Medika Lestari Hospital outpatient unit on 28 July 2021. We evaluated 4 main dimensions, namely: (1) Efficiency, (2) Convenience; (3) Cleanliness; and (4) Financing. The survey instrument was prepared based on the consensus of the research team and has good validity and reliability based on the Pearson and Cronbach–alpha tests. All statistical analyzes were performed with SmartPLS software version 3.3.3. A total of 206 patients were recruited, with a composition of 102 (49.51%) males and 104 (50.49%) females. There were 43 (20.87%), 103 (50%), 46 (22.33%), and 14 (6.80%) patients, respectively, in the age categories 18-25 years, 26–35 years, 36–45 years, and 46–59 years, respectively. We found that the average patient satisfaction with outpatient services at Medika Lestari Hospital was 4.23 (84.6%). The average patient satisfaction score for the outpatient service at the Medika Lestari Hospital is 4.23±0.363. In addition, we also found that service efficiency, cost, cleanliness of the service room, and comfort of the service room had a positive effect on patient satisfaction in the outpatient unit at Medika Lestari Hospital.